The relationship between GDP and the size of the informal economy: Empirical evidence for Spain - Pablo Duarte (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2014)
The empirical evidence on the linkage of the informal economy and GDP is ambiguous. It depends on the method used to estimate the size of the informal economy. I propose a common factor of four different approximations of the size of the informal economy as an alternative. Using Spain as an example I find that GDP Granger-causes informality, but not the other way around. I also find that positive GDP shocks induce positive and statistically significant responses of the size of the informal economy.
Keywords: C38; O17; 330; informal economy; dynamic factor model